Menjawab Krisis Kesehatan Mental Remaja: Sebuah Kajian Literatur tentang Peran Cognitive Behavior Therapy dalam Satu Dekade Global - Nurhaliza, Siti (Universitas Muhammadiyah Metro, 2026)
The adolescent mental health crisis, characterized by the rising prevalence of anxiety, depression, and academic stress, necessitates empirically validated psychological interventions. This study aims to analyze the effectiveness of Cognitive Behavioral Therapy (CBT) as a primary approach for addressing mental health issues among adolescents. Employing a Systematic Literature Review (SLR) methodology, the research analyzes eight Scopus-indexed scientific articles. Results indicate that CBT significantly reduces symptoms of anxiety and depression while enhancing adolescents’ emotion regulation skills. The approach’s flexibility is further demonstrated by its adaptation across diverse service contexts, including digital interventions such as computerized CBT (C-CBT) and internet-based CBT (ICBT). As an effective and adaptable evidence-based intervention for improving adolescent mental well-being, CBT is recommended for integration into psychological support programs in both clinical and educational settings.